Clinical inertia in the treatment of hyperglycemia in type 2 diabetes patients in primary care. (November 2013) - Mata-Cases, Manel; Benito-Badorrey, Belén; Roura-Olmeda, Pilar; Franch-Nadal, Josep; Pepió-Vilaubí, Josep Maria; Saez, Marc; Coll-de-Tuero, Gabriel; ,
Abstract Objective: To assess clinical inertia, defined as failure to intensify antidiabetic treatment of patients who have not achieved the HbA1c therapeutic goal (≤7%). Research design and methods: Multicenter cross-sectional study. Clinical inertia was assessed in a random sample of type 2 diabetes mellitus (T2DM) patients seen in primary care centers. Results: A total of 2783 patients (51.3% males; mean age: 68 [±11.5] years; diabetes duration: 7.1 [±5.6] years; mean HbA1c: 6.8 [±1.5]) were analyzed. Of those, 997 (35.8%) had HbA1c >7%. Treatment was intensified in 66.8% and consisted of: dose increase (40.5%); addition of oral antidiabetic (45.8%); or insulin treatment initiation (3.7%). Mean HbA1c values in patients for whom treatment was intensified vs. non-intensified were 8.4% (±1.2) vs. 8.2% (±1.2), p < 0.05. Clinical inertia was detected in 33.2% of patients and diminished along with treatment complexity: lifestyle changes only (38.8%), oral monotherapy (40.3%), combined oral antidiabetics (34.5%), insulin monotherapy (26.1%) and combination of insulin and oral antidiabetics (21.4%). Clinical inertia decreased as HbA1c increased: 37.3% for HbA1c values ranging between 7.1%–8%; 29.4% for the 8.1%–9% HbA1c range and 27.1% for HbA1c ≥9%. Multivariate analysis confirmed that diabetes duration, step of treatment and HbA1c were related to inertia. For each unit of HbA1c increase clinical inertia decreased 47% (OR: 0.53). Limitations: The retrospective design of the study precluded an accurate investigation about reasons for lack of intensification that could actually be justified by some patient conditions, especially patients' lack of adherence. Conclusions: Clinical inertia affected one third of T2DM patients with poor glycemic control and was greater in patients treated with only lifestyle changes or oral monotherapy. Treatment changes were performed when mean HbA1c values were 1.4 points above therapeutic goals.